Uterine Perforation as a Complication of Manual Vacuum Aspiration for First Trimester Incomplete Abortion - Befkene Wayessa, Muleta; REGASSA FEYISSA, FEKADU; SISAY CHALA, ANTENEH (Ethiopian Journal of Reproductive Health, 2025)
Uterine perforation is a rare but critical complication during intrauterine procedures, including Manual Vacuum Aspiration (MVA) for first-trimester incomplete abortions. This case report details a 24-year-old woman who experienced uterine perforation during MVA, presenting with acute abdominal pain and vaginal bleeding. Diagnostic imaging revealed a uterine defect with an incarcerated omentum. Prompt surgical intervention and antibiotic therapy were administered, ensuring patient recovery. This case underscores the necessity for meticulous preoperative assessment to know the uterine position and the importance of skilled healthcare providers during MVA to minimize the risk of uterine perforation. Continuous training and adherence to best practices are crucial for enhancing patient safety and outcomes.